2008
DOI: 10.4278/ajhp.07043042
|View full text |Cite
|
Sign up to set email alerts
|

The Environment and Urban Adolescents' Use of Recreational Facilities for Physical Activity: A Qualitative Study

Abstract: Previous research points to the importance of increasing facility availability as a means of promoting physical activity, particularly in minority communities in which availability is disproportionately limited. This study shows that, while availability is important, additional facility characteristics should be considered when using environmental change to promote facility use for physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
85
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(113 citation statements)
references
References 29 publications
14
85
3
2
Order By: Relevance
“…Perceptions of neighborhood park quality were measured on a 5-point scale (10strongly disagree and 50strongly agree) using seven items adapted from previous qualitative and quantitative research [7,16,32,35,[50][51][52]. Respondents indicated their agreement with statements about "parks in their neighborhood" that related to cleanliness, availability of facilities of interest, how well used the parks are, attractiveness, safety, maintenance, and the extent to which parks are a benefit to the neighborhood (see Table 3 for full items).…”
Section: Methodsmentioning
confidence: 99%
“…Perceptions of neighborhood park quality were measured on a 5-point scale (10strongly disagree and 50strongly agree) using seven items adapted from previous qualitative and quantitative research [7,16,32,35,[50][51][52]. Respondents indicated their agreement with statements about "parks in their neighborhood" that related to cleanliness, availability of facilities of interest, how well used the parks are, attractiveness, safety, maintenance, and the extent to which parks are a benefit to the neighborhood (see Table 3 for full items).…”
Section: Methodsmentioning
confidence: 99%
“…Neighbourhood parks are the most common venue for physical activity, and residents can assess them at no cost. Several factors have been identified that influence the use of neighbourhood parks for physical activity such as environmental characteristics, individual characteristics and social characteristics (Loukaitou-Sideris, 2004;Ries et al, 2008). However, the influence of environmental characteristics is an issue that is poorly understood (Humpel et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The participants in a study conducted by Aniza and Fairuz (2009) reported that poor air quality, the far distance of the park and the unsafe of the jogging track were the factors that discourage them from physical activity participation. In another study, Ries et al (2008) identified four dimensions of the environment that can affect the use of recreational facilities: physical, social, organisation and economic. They conclude that increasing facility availability may promote physical activity and decrease the risk of obesity.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations